On Reason and the Power of Life (Tolstoy contra Spinoza): (Lev Tolstoy against Spinoza) - Klimova, Svetlana (Problemos, 2021)
In his search for the meaning of life, Tolstoy turned to Spinoza’s rationalist teaching about freedom, reason, morality, and religious faith. Spinoza created a philosophy where beliefs are in union with deeds, logic unites with ethics, and knowledge joins faith. According to Tolstoy, it is art that makes a synthesis of all the best attempts of the real, true philosophy. I argue that Tolstoy’s artistic method of linkage (stseplenie) was probably borrowed from Spinoza. Inspired by Spinoza’s “theorems of reason,” Tolstoy created his own “axiom of life” and elaborates on the concept of the “power of life” as a core of religious faith. Tolstoy endorsed Spinoza’s rationalistic critique of religion which helped to liberate true faith from the power of superstition and church dogmatics, but he criticised the geometric form in which Spinoza put the truths he discovered.
Keywords: faith; reason; the power of life; the meaning of life; linkage; rationalism